Does individualism matter for hedge funds? A cross-country examination - Dai, Na; Nahata, Rajarishi; Brauner, Aaron (Journal of Corporate Finance, 2022)
We examine how individualism, a cultural attribute that emphasizes autonomy, ability, and self-belief, affects hedge funds (HFs). Using Hofstede's framework, we show HFs located in individualistic (IDV) cultures structure their contracts with more performance-driven incentives, take greater risk, and herd less. Individualism also influences risk-shifting behavior: after initial underperformance, HFs increase risk-taking in high IDV cultures. Yet, HFs do not outperform in individualistic countries and draw lower Sharpe ratios, which highlights the link between individualism and overconfidence/over-optimism. Interestingly, HFs' survival is less sensitive to performance in individualistic cultures, again consistent with greater autonomy and opportunities in these countries.